Plantabilidade e sua relação com a produtividade do feijoeiro comum (Phaseolus Vulgaris L.) de segunda safra - Bisognin, Mateus Bortoluzi (2018)
Brazil is the third largest producer of beans in the world and the second largest consumer. The determination of the effect of different variation coefficients on the longitudinal distribution of seeds on the crop grain yield is essential, because the better plants are distributed in the sowing line, the less competition between them for water, light and nutrients. The objective of this study was to evaluate the productivity of a second harvest bean considering different coefficients of variation in the sowing line in an latosol conducted in a no - tillage system. The experiment was conducted in Jaboticaba / RS during 2017. The experimental design was a randomized block design, with four replications, and four variability levels were evaluated in the spatial distribution of seeds in the line, equivalent to 0, 20, 40 and 60% coefficient of variation (CV). The 0% CV treatment was equivalent to the desired uniform distribution of plants (10 plants per linear meter, spaced 10 cm apart). For the other treatments with errors in distribution (20, 40 and 60% of CV), the calculation departed through distances between predetermined plants, thus finding the due CV. Nine components of yield and crop grain yield were evaluated. The data were submitted to a variance analysis, by the F test, at a significance level of 5% and 1%. When the treatment was significant, polynomial regression analysis (p <0.05) was performed. Pearson's linear correlation analysis was also performed. The grain yield reduces linearly with the increase of CV in the distribution of bean seeds. For each 20% increase in CV of seed distribution there is a decrease of 163 kg ha-1 in grain yield. The component that best explains the CV effect of seed distribution on grain yield is the number of grains per plant (r = 0.94). Thus, a correct distribution of seeds in the sowing line should be recommended, and it has as consequence the increase of crop productivity and profitability.